Multiplatform of SVC Device for User Experience Mobile Robot Teleoperation - Muhammad, Fadil; Masjudin (The Indonesian Journal of Computer Science, 2023)
The industrial revolution 4.0 and the rapid advancement of technology during pandemic era has made significant progress in robot industry. There are three types of robots based on the level of independent control such as autonomous mobile robots, semi-autonomous mobile robots, and controller mobile robots. Semi-autonomous mobile robot and Controlled mobile still require human intervention in carrying out the tasks. In this study, teleoperation on mobile robots is displayed on various platforms such as Smartphone, Virtual reality headset as a virtual reality platform, and Computer (SVC) device. A camera is used as a visual sensor that dispatches the information of the surroundings to each platform. The controller used for the teleoperation varies depending on the platforms. The computer platform uses the arrow key on the keyboard. The smartphone platform uses touchscreen. Virtual reality uses Oculus Touch that has been integrated with Oculus Quest 2. ROS# as a robot API framework with Unity engine is used for the communication process between the robot and each platform. Teleoperation Experiments on SVC devices refer to four parameters including task completion rates, task time, satisfaction, and error counts. all these parameters will be combined into a single usability metric (SUM). The SUM results from SVC devices show 54.9% on Smartphones, 79.5% on VR devices, and 90.4% on Computers.